Indian thought and its development - Albert Schweitzer; SCHWEITZER (Albert) (Bombay Wilco Publishing House, 1980)
I have written this short account of Indian Thought and its Development in the hope that it may help people in Europe to become better acquainted than they are at present with the ideas it stands for and the great personalities in whom these ideas are embodied. To gain an insight into Indian thought, and to analyse it and discuss our differences, must necessarily make European thought clearer and richer. If we really want to understand the thought of India we must get clear about the problems it has to face and how it deals with them. What we have to do is to set forth and explain the process of development it has passed through from the time of the Vedic hymns down to the present day. I am fully conscious of the difficulty of describing definite lines of development in a philosophy which possesses in so remarkable a degree the will and the ability not to perceive contrasts as such, and allows ideas of heterogeneous character to subsist side by side and even brings them into connection with each other. But I believe that we, the people of the West, shall only rightly comprehend what Indian thought really is and what is its significance for the thought of all mankind, if we succeed in gaining an insight into its processes.
Keywords: Western and Indian Thought; Teaching of Upanishads; Budhha and his Teaching; Bhakti Mysticism